Answer:
Q' = (-3, 3)
R' = (-5, -3)
S' = (-2, -2)
T' = (0, 1)
Explanation:
The coordinates of the vertices of the quadrilateral are;
T(-2, 1), Q(1, 3), S(0, -2), R(3, -3)
Therefore, taking the operation on the right first, we have;
T(2, 0)QRST, gives;
T(2, 0)QRST→ T(-2 + 2, 1), Q(1 + 2, 3), S(0 + 2, -2), R(3 + 2, -3)
T(2, 0)QRST→ T(0, 1), Q(3, 3), S(2, -2), R(5, -3)
For the next process R y-axis which is the reflection about the y-axis, the preimage (x, y) becomes the image (-x, y)
Therefore, we have;
R y-axis(T(0, 1), Q(3, 3), S(2, -2), R(5, -3)) = T'(0, 1), Q'(-3, 3), S'(-2, -2), R'(-5, -3)
From which we get (Ry-axis
T(2, 0))(QRST = T'(0, 1), Q'(-3, 3), S'(-2, -2), R'(-5, -3).